Non-dengue related febrile thrombocytopenia in HIV patient: a case report - Tanu, Megawati; Suryana, Ketut (International Journal of Advances in Medicine, 2023)
In tropical areas, febrile thrombocytopenia is often caused by infectious diseases, especially dengue. Thrombocytopenia is common in Human Immunedeficiency Virus (HIV) patients at any stage or as a complication of the illness. Here we presented a case report of a 38-year-old female initially diagnosed with dengue fever but turn out to be thrombocytopenia due to HIV infection with pneumocystis carini pneumonia (PCP). Febrile thrombocytopenia in people living with HIV should be observed carefully. It may be caused by a new opportunistic infection or as the natural progression of HIV disease.